Transcriptome Analysis Reveals Docosahexaenoic Acid and α-Linolenic Acid Affect Cholesterol Metabolism and Migration of Monocytes via Common and Distinct Gene Pathways. (7th June 2021) - Rodway, Lisa; Pauls, Samantha; Aukema, Harold; Taylor, Carla; Zahradka, Peter
Abstract: Objectives: One of the earliest events in atherosclerotic plaque formation is the migration of monocytes to damaged blood vessels, and the accumulation of cholesterol in monocyte-derived macrophages. The omega-3 fatty acid docosahexaenoic acid (DHA) is known to inhibit this process. While there is limited evidence suggesting α-linolenic acid (ALA) has a similar effect, ALA has not been directly compared to DHA. The primary objective of this study was to compare the gene expression profiles of monocytes that have been exposed to either ALA or DHA and examine the effect of these fatty acids on monocyte cholesterol content and migration in a cell culture model. Methods: Transcriptome analysis was performed on total mRNA isolated from human THP-1 monocytes treated with ALA, DHA or vehicle for 48 h. Candidate genes identified via fold change and Ingenuity Pathway Analysis were validated by qPCR. Functional assays to measure total cholesterol content and migration were then performed on monocytes treated with ALA or DHA. Results: Transcriptome analysis identified a series of genes associated with cholesterol metabolism and cell migration altered by ALA and DHA treatment. Changes in mRNA levels for candidate genes were validated by qPCR, with similar expression patterns as in the transcriptome analysis. Based on these data, both fatty acids were predicted to reduce cholesterol synthesis, ALA would increase migration and DHA would have no effect. Functional assays were then performed and revealed that ALA and DHA decreased cholesterol content to a similar extent. Additionally, contrary to our predictions, DHA significantly decreased migration, while ALA had no effect. Conclusions: The results suggest ALA and DHA may influence monocyte migration through distinct gene pathways, while cholesterol metabolism may be regulated by a common mechanism. Furthermore, only DHA treatment reduced monocyte migration in functional assays, while both fatty acids reduced cholesterol content. Due to the critical role of monocyte migration and cholesterol content in the pathophysiology of atherosclerosis, it may be concluded from this study that both DHA and ALA may exert protective effects involving different mechanisms as they relate to individuals at risk for cardiovascular disease. Funding Sources: CIHR, NSERC